Strategi Ayah dalam Membangun Budaya Santun Anak di Keluarga Kristiani - Kosma Manurung; Sudirman (Sekolah Tinggi Agama Kristen Samarinda, 2023)
Abstract: Polite children are highly desired, hoped for, also needed by parents, extended families, communities, and God's church. Good manners are important for children to have, apart from being a superior character associated with their social intelligence, they are also a surefire recipe for building and maintaining social relationships, and are very connected to the brightness of a child's future. This article is intended to examine the strategy of fathers in building cultural support for children in Christian families. The narrative qualitative method and literature review were chosen in working on this article with the hope of being able to get a strong, systematic meaning, and have an academic foundation when discussing biblical narratives about politeness, the importance of politeness for a child, and father's strategies in building a polite culture in children. It was concluded that a father will play an optimal role in building a culture of politeness in children when he makes himself the main channel of children's education, forbids it at the child's level of understanding and uses the child's love language, and makes himself the closest model of politeness that can be seen by children.Abstrak: Anak yang santun sangat diinginkan, diharapkan, juga dibutuhkan baik oleh orang tua, keluarga besar, komunitas masyarakat, maupun gereja Tuhan. Sopan santun penting anak-anak miliki selain karena itu merupakan karaker unggul yang terafiliasi dengan kecerdasan sosialnya juga merupakan resep jitu dalam membangun dan mempertahankan hubungan sosial, serta sangat berkaitan dengan kecerahan masa depan anak. Artikel ini bermaksud mencermati strategi ayah dalam membangun budaya santun pada anak di keluarga Kristiani. Metode kualitatif naratif dan kajian literatur dipilih dalam mengarap artikel ini dengan harapan mampu mendapatkan makna yang kuat, sistimatik, dan memiliki landasan akademik ketika membahas terkait narasi Alkitab tentang kesantunan, arti penting kesantunan bagi seorang anak, dan strategi ayah dalam membangun budaya santun pada anak. Disimpulkan bahwa seorang ayah akan berperan maksimal dalam membangun budaya santun pada anak ketika menjadikan dirinya saluran utama dari pendidikan anak, mengajarkannya pada tingkat pemahaman anak dan menggunakan bahasa cinta anak, serta menjadikan dirinya role model kesantunan yang paling dekat yang bisa di lihat oleh anak.